2018 16th Annual Conference on Privacy, Security and Trust (PST) 2018
DOI: 10.1109/pst.2018.8514196
|View full text |Cite
|
Sign up to set email alerts
|

xLED: Covert Data Exfiltration from Air-Gapped Networks via Switch and Router LEDs

Abstract: In this paper we show how attackers can covertly leak data (e.g., encryption keys, passwords and files) from highly secure or air-gapped networks via the row of status LEDs that exists in networking equipment such as LAN switches and routers. Although it is known that some network equipment emanates optical signals correlated with the information being processed by the device ('side-channel'), intentionally controlling the status LEDs to carry any type of data ('covert-channel') has never studied before. A mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 28 publications
(30 reference statements)
0
33
0
Order By: Relevance
“…In 2017, Guri et al presented LED-it-GO, a covert channel that uses the hard drive (HDD) indicator LED in order to exfiltrate data from air-gapped computers [21]. Guri et al also presented a method for data exfiltration from airgapped networks via router and switch LEDs [36]. In the case of HDDs and routers, the devices blinks frequently, and hence, the transmissions performed via these channels will not raise the user's suspicious.…”
Section: Opticalmentioning
confidence: 99%
“…In 2017, Guri et al presented LED-it-GO, a covert channel that uses the hard drive (HDD) indicator LED in order to exfiltrate data from air-gapped computers [21]. Guri et al also presented a method for data exfiltration from airgapped networks via router and switch LEDs [36]. In the case of HDDs and routers, the devices blinks frequently, and hence, the transmissions performed via these channels will not raise the user's suspicious.…”
Section: Opticalmentioning
confidence: 99%
“…They showed that a malware can indirectly control the hard drive LED at a rate of 5800Hz which exceeds the visual perception capabilities of humans. In 2018, Guri et al demonstrated a malware which can leak data from air-gapped networks via switch and router LEDs [18]. Guri et al presented a covert channel for leaking data through air-gaps using IR (Infrared) light and security cameras [19].…”
Section: B Opticalmentioning
confidence: 99%
“…In this paper we also examine an optical sensor capable of sensing the light emitted from the keyboard LEDs. Such sensors are used extensively in VLC (visible light communication) and LED to LED communication [18]. Notably, optical sensors are capable of sampling LED signals at high rates, enabling data reception at a higher bandwidth than a typical video camera.…”
Section: B Receivermentioning
confidence: 99%
“…In 2017, Guri et al presented LED-it-GO, a covert channel that uses the hard drive indicator LED in order to exfiltrate data from air-gapped computers [32]. Guri et al also presented a method for data exfiltration from air-gapped networks via router and switch LEDs [30]. Data can also be leaked optically through fast blinking images or low contrast bitmaps projected on the LCD screen [21].…”
Section: Opticalmentioning
confidence: 99%